Issues in contemporary zakah: a juristic analytical evaluation - Haneef, Sayed Sikandar Shah; Mahmud , Mek Wok (IIUM Press, 2011)
This book presents a juridical analytical evaluation of the issues pertaining to zakah as raised and debated by academics with interest on the subject in contemporary time. In articulating these issues from the fiqh perspective, it argues that any discussion of the jurisprudence of zakah based on economic imperatives cannot and should not supersede the immutable framework of its legislation along with its divinely ordained socio-economic goals.